Assessing the reality of the strategic diversification of human resources management in non-governmental organizations: A Case Study (University of Al-Qalam College) - Saab Salamah, Majid; F. Khursheed, Jwan (International Journal of Psychosocial Rehabilitation, 2020)
Diversity is treated as a blessing from Allah, in which organizations have a significant diversity of experiences, obtained skills, thinking strategies, and the possibility of presenting new initiatives and ideas as a result of the strategic diversity of human resources that benefits the organization significantly. Moreover, respecting diversity and managing it well can lead to job stability. Productivity can also be increased, whether at the level of individuals or departments, because when individuals from various groups feel appreciation, justice, and equality in working, they will make every effort to raise the level of performance. Perhaps creativity and making up something new is the basic element of competition in today’s world. Members of various groups usually attempt to prove their presence through perseverance. From this launching point, the current study aims at demonstrating the possibility of evaluating the strategy for human resources in the organization researched in Kirkuk governorate. After field visiting the organization and learning the mechanism of dealing with and interviewing the general managers there, the data and required information were collected by depending on the examination list. After collecting the data, it is analyzed by means of the Excel program. In light of the results of the analysis, the study can reach a number of conclusions and recommendations that suit the nature of the study.